A concepção de representação (carto)gráfica para Roger Brunet: aportes para o desenvolvimento da Cartografia Geográfica Crítica - Eduardo Paulon Girardi (Confins)
In this article, we review the conception of (carto)graphic representation in Roger Brunet's main works and analyze it in the context of the development of Critical Geographic Cartography, seeking elements that subsidize advances in our proposal, especially elements that indicate the potential of corematics/graphic modeling for geographic analysis and discourse and the subjectivity inherent in graphic models and map-models. We highlight the approximations of chorematic/graphic modeling with the principles of cartographic visualization and with Brian Harley's critical map theory. An approximation between Brunet's and Harley's proposals is presented at the end of the article.